Cyto- and Genotoxicity assessment of manufactured nano cerium dioxide in the A549 cell line - Saruga, Andreia (2016)
In the past decades the growing application of nanomaterials (NMs) in diverse consumer products has raised various concerns in the field of toxicology. They have been extensively used in a broad range of applications and cover most of the industrial sectors as well as the medicine and the environmental areas. The most common scenarios for human exposure to NMs are occupational, environmental and as consumers and inhalation is the most frequent route of exposure, especially in occupational settings. Cerium dioxide NMs (nano-CeO2) are widely used in a number of applications such as in cosmetics, outdoor paints, wood care products as well as fuel catalysts. For such reason, nano-CeO2 is one of the selected NMs for priority testing within the sponsorship program of the Working Party of Manufactured Nanomaterials of the OECD. In this context, the aim of this study is to assess the safety of nano-CeO2 (NM-212, Joint Research Center Repository) through the characterization of its cytotoxicity and genotoxicity in a human alveolar epithelial cell line. A dispersion of the NM in water plus 0.05% BSA was prepared and sonicated during 16 minutes, according to a standardized protocol. DLS analysis was used to characterize the quality of the NM dispersion in the culture medium. To evaluate the cytotoxicity of nano-CeO2 in the A549 cell line, the colorimetric MTT assay was performed; the capacity of cells to proliferate when exposed to CeO2 was also assessed with the Clonogenic assay. The genotoxicity of this NM was evaluated by the Comet Assay (3 and 24h of exposure) to quantify DNA breaks and the FPG-modified comet assay to assess oxidative DNA damage. The Cytokinesis-Block Micronucleus (CBMN) assay was used to further detect chromosome breaks or loss. The nano-CeO2 particles are spherical, displaying a diameter of 33 nm and 28 m2/g of surface area. The results of the MTT assay did not show any decreased in cells viability following treatment with a dose-range of nano-CeO2 during 24h. Nevertheless, the highest concentrations of this NM were able to significantly reduce the colony forming ability of A549 cells, suggesting that a prolonged exposure may be cytotoxic to these cells. Data from both genotoxicity assays revealed that nano-CeO2 was neither able to induce DNA breaks nor oxidative DNA damage. Likewise, no significant micronucleus induction was observed. Taken together, the present results indicate that this nano-CeO2 is not genotoxic in this alveolar cell line under the tested conditions, although further studies should be performed, e.g., gene mutation in somatic cells and in vivo chromosome damage (rodent micronucleus assay) to ensure its safety to human health.